MEMPREDIKSI PENYIMPANGAN INTERPERSONAL DARI KEADILAN PROSEDURAL DAN KEADILAN INFORMASIONAL - Ema Nurmaya (Universitas Ahmad Dahlan, 2020)
This study aims to investigate the relationship between procedural and informational justice and interpersonal deviations. Specifically, this study hypothesizes that: (a) There is a negative relationship between procedural justice and interpersonal deviation behavior, (b) There is a negative relationship between informational justice and interpersonal deviationbehavior. To test the hypothesis, SPSS was used to analyze survey data from 124 hospital nurses at public private hospitals in Yogyakarta. The results show that all hypotheses are proven. And furthermore, this study produces suggestions both theoretically and practically.